A new approach to assessment of reproductive losses of the first trimester of pregnancy - N. A. Ishutina (Scientific Сentre for Family Health and Human Reproduction Problems, 2021)
Background. At present, the role of cytomegalovirus infection in the disruption of acental formation and associated pathological conditions of the fetus is bvious, which are based on oxidative and inflammatory reactions that cause disruption of igration and invasion of trophoblasts, angiogenic modulation of placental and uterine vessels.Objective: To analyze the quantitative indicators of hypoxia-inducible factor 1α, α-tocopherol and docosahexaenoic acid in the peripheral blood in comparison with morphological changes in the placenta and uterine mucosa in seropositive women with spontaneous abortion associated with reactivation of ytomegaloviral infection.Methods: Studies were carried out at 7-9 weeks of gestation. 67 observations were analyzed, including 35 seropositive women in the first trimester with spontaneous abortion associated with reactivation of cytomegaloviral infection and 32 healthy seronerative women with voluntary termination of pregnancy. Stabilized blood from vein, epithelium of the inner surface of the cheek, cervical canal, urine, villous chorion, and uterine mucosa were used as the test material. Enzyme immunoassay was used to detect serological markers of cytomegaloviral infection (CMV-IgG/IgM antibodies, CMV-IgG avidity), hypoxia-induced factor 1α, α-tocopherol – by fluorometric method, PCR (polymerase chain reaction) in real time – DNA CMV, the method of gas-liquid chromatography – docosahexaenoic acid, histological methods – the general plan of the structure of the chorionic villus and the mucous membrane of the uterus.Results: In seropositive women with spontaneous abortion associated with reactivation of cytomegaloviral infection, the average of hypoxia-induced  factor 1α was 1.54 times higher, α-tocopherol and docosahexaenoic acid were 1.71 times lower and 1.40 times lower (p < 0.001, respectively) than in the group of eronegative women. Strong inverse correlations were revealed. Morphologically, there were signs of delayed formation of villi, decidualization of the endometrial stroma and the formation of uteroplacental vessels. Conclusion. In seropositive women with spontaneous abortion associated with reactivation of cytomegaloviral infection, a strong association of high HIF-1α values with decrease in α-tocopherol and docosahexaenoic acid in the peripheral blood was revealed, which can be considered as an unfavorable factor in the disruption of placenta formation.